2022
DOI: 10.1038/s41467-022-33513-4
|View full text |Cite
|
Sign up to set email alerts
|

A NAC-EXPANSIN module enhances maize kernel size by controlling nucellus elimination

Abstract: Maize early endosperm development is initiated in coordination with elimination of maternal nucellar tissues. However, the underlying mechanisms are largely unknown. Here, we characterize a major quantitative trait locus for maize kernel size and weight that encodes an EXPANSIN gene, ZmEXPB15. The encoded β-expansin protein is expressed specifically in nucellus, and positively controls kernel size and weight by promoting nucellus elimination. We further show that two nucellus-enriched transcription factors (TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In light of what presented here, we believe that this hypothesis should be revised in favor of a role of HG de-methylesterification in initiating cell wall degradation. Consistent with our results, Qin Sun et al showed that the maize EXPANSIN B15, a protein responsible for cell wall loosening, promotes the process of nucellus elimination ( 33 ). We speculate that expansins might facilitate the work of PME and PLL enzymes by relaxing the cell wall.…”
Section: Discussionsupporting
confidence: 92%
“…In light of what presented here, we believe that this hypothesis should be revised in favor of a role of HG de-methylesterification in initiating cell wall degradation. Consistent with our results, Qin Sun et al showed that the maize EXPANSIN B15, a protein responsible for cell wall loosening, promotes the process of nucellus elimination ( 33 ). We speculate that expansins might facilitate the work of PME and PLL enzymes by relaxing the cell wall.…”
Section: Discussionsupporting
confidence: 92%
“…To determine the developmental defects, paraffin sections of the WT and mn7 immature kernels were observed at 13 and 24 days after pollination (DAP). At an early stage of maize kernel development, nucellus maternal tissue degenerates through programmed cell death (PCD), which allows the contents of the dying cells to remobilize and nourish the developing embryo and endosperm (Dominguez and Cejudo, 2014 ; Sun et al ., 2022 ). Compared with the nucellus in the WT, which was completely degraded at 13 DAP, we found a relatively large nucellus surrounding the endosperm in mn7 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the transcription factor MaBSD1 regulates MaEXP1 and MaEXP2 expression in response to banana ripening ( Ba et al., 2014 ). ZmNAC11 and ZmNAC29, two NAC transcription factors in maize, can activate ZmEXPB15 expression, thereby improving grain size and weight by regulating nuclear elimination ( Sun et al., 2022 ). To elucidate the transcriptional regulatory mechanism of CmEXPB1 , we predicted its interacting transcription factors and identified 56 transcription factors that may regulate CmEXPB1 expression positively or negatively ( Figure 8A ).…”
Section: Discussionmentioning
confidence: 99%